The Diagnostic Accuracy of One-Step Nucleic Acid Amplification for Lymph Node Metastases of Papillary Thyroid Carcinoma： A Systematic Review and Meta-Analysis - Wang, Xiaofei; Zheng, Xun; Zhu, Jingqiang; Li, Zhihui; Wei, Tao (Frontiers in Endocrinology, 2022)
Background: One-step nucleic acid amplification (OSNA) analysis is a molecular diagnostic technique for lymph node metastases (LNMs) by quantifying cytokeratin 19(CK 19) mRNA. We aim to evaluate the intraoperative diagnostic accuracy of OSNA assay for LNMs of papillary thyroid carcinoma (PTC). Methods: PubMed, Embase, Cochrane Library, and Web of Science databases were searched to retrieve related literature. A meta-analysis was performed using STATA11.0, Meta-Disc 1.4 and RevMan 5.3. Results: This meta-analysis included six studies involving 987 lymph nodes from 194 patients. The pooled sensitivity, specificity, and area under the summary receiver-operating characteristic curve (AUC) of OSNA for detecting LNM were 0.88, 0.90, and 0.95, respectively. Conclusion: OSNA assay is an accurate molecular diagnosis for intraoperative detection of lymph node metastasis in PTC.